Pore habit of methane hydrate and its evolution in sediment matrix – Laboratory visualization with phase-contrast micro-CT - Lei, Liang; Seol, Yongkoo; Choi, Jeong-Hoon; Kneafsey, Timothy J. (Marine and petroleum geology, 2019)
Describing the pore habit of methane hydrate in sediment matrices is essential for understanding natural distribution of methane hydrate, methane trace (transport and solidification) in the hydrate stability zone, physical properties of hydrate-bearing sediments, and the associated influence on potential gas production. Pore habit visualization in natural media at pore scale even with laboratory synthesized cores has been challenging due to the similar densities of methane hydrate from pore liquid. In this work, we used phase-contrast assisted micro-CT with potassium iodine-doped brine to visualize four phases: sand particles, pore fluid, methane hydrate and methane gas. This study visualizes the pore habit of methane hydrate at various stages including during hydrate formation in excess-gas systems, its evolution after brine injection to replace pore fluid, and hydrate formation in excess-water systems. Hydrate tends to adopt round and smooth surfaces when in contact with water while exhibits relatively angular interfaces when in contact with methane gas. Hydrate formation in excess-gas systems results in a partial cementing and partial mineral-coating pore habit, while hydrate in excess-water systems develops mainly as pore-filling, and locally cementing or mineral-coating where big gas pockets exist at the initial state. Pore liquid replacement from methane gas to brine triggers a shift of hydrate pore habit towards pore-filling. Methane hydrate evolution over time produces bigger hydrate particles but with less contact area with sand particles. The effects of hydrate pore habit become less important as hydrate particle size exceeds the pore size. Additionally, hydrate formation could trap residual methane gas and brine as inclusions. •Excess-gas systems host primarily cementing and mineral-coating hydrate.•Excess-water systems develop mainly pore-filling hydrate.•Brine injection into excess-gas systems shifts pore habits towards pore-filling.•The affinity to quartz sand surface follows the order: water > hydrate > gas.•Natural gas hydrate could be: round, similar in size, mainly pore-filling.